Capital Market Research in Accounting: Evidence from The Tehran Stock Exchange - Mohammad Namazi; Amin Nazemi (Asian Academy of Management Journal of Accounting and Finance, 2009)
The major purpose of this study is to classify and analyse capital market research conducted in the Tehran Stock Exchange Market (TSEM). Similar to Namazi and Nazemi’s (2005) review of Finance Studies on the TSEM in 1991–2003, we review, classify and analyse the significant Accounting Studies related to the TSEM. Consequently, by both employing content analysis and archival methodology and considering academic accounting courses and programs established by the Ministry of Science, Research and Technology (MSRT), the studies are classified into four main topics: financial accounting, auditing, managerial accounting and other subjects. The significant results reported in each of the above groups of studies are presented. It is concluded that, in recent years, the amount of research conducted and the research techniques utilised concerning TSEM-related accounting issues have rapidly improved in various significant aspects of the capital market; yet, much more in-depth research must be carried out.